2010
DOI: 10.1152/ajpgi.00322.2009
|View full text |Cite
|
Sign up to set email alerts
|

The hepatic response to FGF19 is impaired in patients with nonalcoholic fatty liver disease and insulin resistance

Abstract: Intestinal FGF19 has emerged as a novel endocrine regulator of hepatic bile salt and lipid metabolism. In patients with nonalcoholic fatty liver disease (NAFLD) hepatic lipid metabolism is deranged. A possible role of FGF19 in NAFLD has not been reported yet. In this study, we assessed intestinal FGF19 production and the hepatic response to FGF19 in NAFLD patients with and without insulin resistance [homeostasis model of assessment (HOMA) score > or =2.5 (n = 12) and HOMA score <2.5 (n = 8), respectively]. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
111
4
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(131 citation statements)
references
References 34 publications
12
111
4
4
Order By: Relevance
“…Fgf15 knockout mice showed glucose intolerance, increased hepatic gluconeogenesis, and reduced hepatic glycogen storage but unaltered overall insulin sensitivity. Decreased fasting FGF19 levels or impaired hepatic response to FGF19 have been reported in humans with fatty liver and insulin resistance (Schreuder et al, 2010;Wojcik et al, 2012). These studies suggest that bile acid regulation of hepatic glucose metabolism involves complex cross-talk between FXR-dependent pathways and FXR-independent signaling pathways.…”
Section: Bile Acid Receptor Signaling In Liver Metabolismmentioning
confidence: 74%
“…Fgf15 knockout mice showed glucose intolerance, increased hepatic gluconeogenesis, and reduced hepatic glycogen storage but unaltered overall insulin sensitivity. Decreased fasting FGF19 levels or impaired hepatic response to FGF19 have been reported in humans with fatty liver and insulin resistance (Schreuder et al, 2010;Wojcik et al, 2012). These studies suggest that bile acid regulation of hepatic glucose metabolism involves complex cross-talk between FXR-dependent pathways and FXR-independent signaling pathways.…”
Section: Bile Acid Receptor Signaling In Liver Metabolismmentioning
confidence: 74%
“…Secreted FGF19 binds to a hepatic membrane receptor complex, FGF19 receptor 4 (FGFR4), and its coreceptor β-Klotho (βKL) (3)(4)(5)(6), and it then triggers the activation of cellular kinases, including ERK and glycogen synthase kinase (GSK), to mediate postprandial metabolic responses (7,8). Interestingly, a recent study showed that the hepatic response to FGF19 is impaired in patients with nonalcoholic fatty liver disease (NAFLD) and insulin resistance (9). Despite the functional importance of βKL in transmitting FGF19 signaling, little is known about how the expression of βKL is regulated and why FGF19 signaling is impaired in patients who have fatty liver.…”
mentioning
confidence: 99%
“…Hepatic miR-34a levels are substantially elevated in human patients with fatty liver (16,17) and in obese mice (14,15). Moreover, hepatic responses to FGF19 are impaired in patients with fatty liver disease (9). Therefore, to test if aberrantly elevated miR-34a in obesity correlates inversely with βKL levels, we determined the miR-34a and βKL levels in two mouse models of obesity.…”
mentioning
confidence: 99%
“…The hepatic response to FGF15/19 is impaired in NAFLD patients with insulin resistance. This impaired response may contribute to the disturbance of lipid homeostasis in NAFLD (Schreuder et al, 2010). Serum FGF21 levels are significantly increased in NAFLD (Yilmaz et al, 2010;Dushay et al, 2010;Li et al, 2010).…”
Section: Endocrine Fgfsmentioning
confidence: 99%